"Principles" Guiding Our Medical ICU. (8th January 2021) - Chatterjee, Souvik; Wright, Scott M.
Abstract : Caring for the critically ill is a humanistic endeavor that requires thoughtful collaboration by a multidisciplinary team. In recent times, patient care in ICUs has become more complex with technological advances in monitoring, diagnostic testing, and therapeutics; many of these advances have translated into improved patient outcomes. In this increasingly complicated system, local culture and goals for the unit can also be overwhelmed by the impersonal and overarching institutional objectives. Developing "ICU specific principles" is a structured approach to cultivate habits and encourage attitudes that are aligned with the values of the team; this can serve to optimize the work environment and prioritize excellent patient care.